Thursday

October 30, 2014

October 30, 2014

Posted by **Bree** on Saturday, March 13, 2010 at 7:49pm.

(dy/dx)-2y+4=0, y(1)=4

- calculus -
**Damon**, Saturday, March 13, 2010 at 10:26pmI am going to use t instead of x. I can do initial condition better that way

let y = a e^kt + b

dy/dt = a k e^kt

a k e^kt -2 a e^kt -2b + 4 = 0

so b = 2

a k = 2 a

k = 2

y = a e^2t + 2

when t = 1, y = 4

4 = a e^2 +2

a e^2 = 2

a = 2/e^2

so

y = (2/e^2) e^2t + 2

y = 2 e^(2t-2) + 2

**Answer this Question**

**Related Questions**

Calculus - Solve the following initial value problem explicitly: y'= ye^-x , y(0...

Calculus - Solve the initial-value problem. y'' - 2y' + y = 0 , y(2) = 0 , y'(2...

calculus - how do you solve the initial value problem by separation of variables...

calculus - solve the initial value problem by separation of variables dy/dx=-x^...

calculus - solve the initial value problem by separation of variables dy/dx=-xy^...

calculus - solve the initial value problem by separation of variables dy/dx=-xy^...

calculus - solve the initial value problem by separation of variables dy/dx=-x^...

calculus - solve the initial value problem by separation of variables 8. dy/dx=x...

calculus - solve the initial value problem by separation of variables dy/dx=y^(2...

Calculus II - Solve the Initial Value Problem: Let k and Po be positive ...